Seeking Begumpura : the social vision of anticaste intellectuals - Omvedt, Gail (Navayana, 2016)
The bhakti radical Ravidas (c 1450Â1520), calling himself a Âtanner now set freeÂ, was the first to envision an Indian utopia in his song ÂBegumpuraÂÂa modern casteless, classless, tax-free city without sorrow. This was in contrast to the dystopia of the brahmanical kaliyuga. Anticaste intellectuals in India posited utopias much before Thomas More, in 1516, articulated a R The bhakti radical Ravidas (c 1450Â1520), calling himself a Âtanner now set freeÂ, was the first to envision an Indian utopia in his song ÂBegumpuraÂÂa modern casteless, classless, tax-free city without sorrow. This was in contrast to the dystopia of the brahmanical kaliyuga. Anticaste intellectuals in India posited utopias much before Thomas More, in 1516, articulated a Renaissance humanist version. Gail Omvedt, in this study, focuses on the worldviews of subaltern visionaries spanning five centuriesÂChokhamela, Janabai, Kabir, Ravidas, Tukaram, the Kartabhajas, Phule, Iyothee Thass, Pandita Ramabai, Periyar and Ambedkar. She charts the development of their utopian visions and the socioeconomic characteristics of the societies conceived through this long period.